Productivity, Growth, and Internationalisation: The Case of German and British High Techs - Helmut Fryges (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
International engagement is often expected to improve firm performance. Especially for small technology-oriented firms, export activities may be important, being regarded as one way to amortise these firms? high product research and development costs. This paper examines the relationship between international business activities and firm performance using a sample of about 200 young high-tech firms in Germany and the UK that were contacted by two surveys in 1997 and 2003. I find out that the performance enhancing effects of internationalisation that were still observed in 1997 are in fact restricted to an early stage of the firms? life cycles and disappear when technology-oriented firms become mature. The results are in line with many other studies: Firms exhibiting superior performance are or will become exporters.
Keywords: F23; L86; L60; L25; 330; High technology industries; internationalisation; firm growth; productivity; switching; Hochtechnologiesektor; Internationale Markteintrittsstrategie; Unternehmenswachstum; Lebenszyklus